Identification of potential vectors of Xylella fastidiosa in Portuguese olive orchards and weeds - Popova, Ganna (2020)
Tese de mestrado em Ecologia e Gestão Ambiental, Universidade de Lisboa, Faculdade de Ciências, 2020